A STUDY ON NEIKURI (OIL DROP TEST IN URINE) IN VATHA SOOLAI - G, Senthilvel (AYUSHDHARA, 2016)
The methodology of diagnosis in Siddha system is based on eight fold examinations of pulse, tactile perception, tongue, color and complexion, speech, eyes, stools and urine. Of all these parameters, Urine examination has gained paramount importance next to pulse examination. Neikuri is a diagnostic tool of urine examination using Sesame oil developed by Siddhars and also throws a light on prognosis of disease condition. This is an attempt to understand the Siddha system of diagnosing pathological conditions which are a non-invasive, highly cost effective procedure which can be used for both diagnostic and prognostic purposes. This study aims to validate the Neikuri image on the patients diagnosed as Vatha Soolai. For the purpose of the study, thirteen urine samples of Vatha Sollai patients were collected and the oil drop test was conducted using the guidelines mentioned the Siddha Literature. Majority of samples showed a small circular shape like Pearl under Kapha humor. This study can be used as referenced diagnostic criteria for Vatha Soolai.